Electricity and energy policy in Britain, France and the United States since 1945 - Chick, Martin 1958- (Edward Elgar, 2007)
Introduction -- Shifting from coal to oil : what price security? -- The European coal and steel community -- Moving the margin to the centre : pricing electricity -- Electricity investment : rewarding the past, discounting the future -- Deregulation, privatisation and liberalisation -- Conclusion